The Structural Design of a Reinforced Concrete Box Culverts - Hasanain S. Al Tamemi; Mohammad R. Habibi; Mohammad H. Tavana (Genius Journals, 2022)
Box − Culverts are an important part and an indispensable structural component in civil engineering, especially when it comes to making this part a link between nature and concrete structures by making box culverts as a bridge to cross vehicles or pedestrians or both and other uses as they are cheap and economical Compared to the construction of a bridge for this purpose. We can see these box culverts in different shapes and types in terms of the materials used for them or the way they are built, where some of them are bricks, stone or concrete, but their types, for example, are in the form of surface bridges or tube or box channels with square walls or triple walls and others depend This depends on the place of use and the loads and loads resulting from the effect of water or the reaction resulting from the soil. To design the box culverts, consideration must be given to the state of the structure, whether it is full or empty, the amount of forces exerted on it, the amount of reactions resulting from the soil and the forces resulting from the movement of water inside the box culverts, as well as the amount of forces applied to the live loads resulting from movement over the box culverts As well as the amount of dead loads for box culverts. All these limitations and others lead to one result, which is the design of box culverts that are characterized by their resistance to conditions and safe for users. The aim of this study is to design reinforced concrete box culverts based on the highest value of positive moments and the highest value of negative moments, in addition to taking the highest amount of shear strength and designing box culverts that can be used well for the purpose of resisting all live and dead loads as well as all forces resulting from water or the soil . All results are manual results and no programs were used in order to achieve the greatest benefit in terms of the accuracy and acceptability of the results during the design
Keywords: Box−Culverts; lateral forces; Moments; thrust